Patient frailty predicts worse perioperative outcomes and higher cost after radical cystectomy. (March 2020) - Palumbo, Carlotta; Knipper, Sophie; Pecoraro, Angela; Rosiello, Giuseppe; Luzzago, Stefano; Deuker, Marina; Tian, Zhe; Shariat, Shahrokh F.; Simeone, Claudio; Briganti, Alberto; Saad, Fred; Berruti, Alfredo; et al.
Abstract: Background: Relatively few studies investigated the importance of frailty in radical cystectomy (RC) patients. We tested the ability of frailty, using the Johns Hopkins Adjusted Clinical Groups indicator, to predict early perioperative outcomes after RC. Methods: RC patients were identified within the National Inpatient Sample database (2000–2015). The effect of frailty, age and Charlson Comorbidity Index were tested in five separate multivariable models predicting: (1) complications, (2) failure to rescue (FTR), (3) in-hospital mortality, (4) length of stay (LOS) and (5) total hospital charges (THCs). All models were weighted and adjusted for clustering, as well as all available patient and hospital characteristics. Results: Of 23, 967 RC patients, 5833 (24.3%) were frail, 7721 (32.2%) were aged ≥75 years and 2832 (11.8%) had CCI ≥2. Frailty, age ≥75 years and CCI ≥2 were non-overlapping in 86.3% of the cohort. Any two or three of these features were recorded in 12.4 and 1.3%, respectively. Frailty was an independent predictor of all five examined endpoints and the magnitude of its association was stronger or at least equal than that of age ≥75 years and CCI ≥2. Conclusion: Frailty, advanced age and comorbidities represent non-overlapping patients' characteristics. Of those, frailty represents the most consistent and strongest predictor of early adverse outcomes after RC. Ideally, all three indicators should be considered in retrospective, as well as prospective analyses. Pre-surgical recognition of frail patients should be ideally incorporate in clinical practice in order to address these patients to multimodal pre-habilitation programs that may potentially improve the perioperative prognosis. Highlights: Age, comorbidities and frailty may worsen perioperative outcomes after radical cystectomy. However, these three features often represent non-overlapping patients' characteristics. Frailty represents the strongest predictor of early adverse outcomes after radical cystectomy. Pre-surgical recognition of frail patients should be ideally incorporate in clinical practice. Frail patients should be addressed to multimodal pre-habilitation programs.